Flavonolignan and flavone inhibitors of a Staphylococcus aureus multidrug resistance (MDR) efflux pump: synthesis and structure activity relationships - Guz, Nathan R., author; Stermitz, Frank R., advisor (Colorado State University. Libraries, 2001)
Multidrug resistance (MDR) represents an increasing problem in the treatment of bacterial infections and cancer. It often appears after prolonged exposure of cells to a single drug and is often characterized by resistance to a series of structurally unrelated compounds. One important resistance mechanism involves drug depletion in cells by transmembrane efflux proteins, for example P-glycoprotein (P-gp) in mammalian cells, Bmr in Bacillus subtilis, and NorA in Staphylococcus aureus. There has been extensive work in the field of mammalian tumor research and a multitude of structure-activity relationship (SAR) studies of P-gp inhibitors have been reported. The identification of bacterial MDR efflux inhibitors is in its infancy and only a limited number have been identified. A potent inhibitor of the NorA efflux pump in the gram-positive bacteria S. aureus was previously isolated from Berberis fremontii and identified as the flavonolignan 5'-methoxyhydnocarpin. This flavonolignan was also reported in the mid 1970's as a minor constituent of Hydnocarpus wightiana, but the authors were unable to report a definitive regiochemical assignment of the 1,4-benzodioxane substituents due to the low resolution and lack of two-dimensional NMR techniques available at that time. A regiocontrolled total synthesis of the flavonolignan was performed and it was shown that the original regiochemical assignments were incorrect. The flavonolignan was renamed 5'-methoxyhydnocarpin-D to denote the correct regiochemistry. Because of the high activity of 5-methoxyhydoncarpin-D, a SAR study of structurally reminiscent synthetic flavonolignans was performed to see if a more potent inhibitor of the NorA efflux pump could be found. Numerous inhibitors were synthesized using a Ag2CO3 mediated biomimetic coupling of various flavonoids and hydroxycinnamyl alcohols. Hydnocarpin-D, 5-deoxyhydnocarpin-D, 5,7-deoxyhydnocarpin-D, and 5-deoxyscutelIaprostin-A proved to be more potent inhibitors of the NorA efflux pump than the natural product. It was also shown that some small lipophilic ether derivatives of 4'-hydroxyflavone were also more potent than 5'-methoxyhydoncarpin-D. Preliminary results from bioassays investigating MDR efflux pump inhibitors of the gram-negative bacteria Escherichia coli and Pseudomonus aeruginosa showed that coumarins may potentiate anthraquinones. Harbouria trachypleura belongs to the Apiaceae, a family of plants known to often contain coumarins. Bioassay results showed that H. trachypleura did not contain the desired inhibitors, but the plant belongs to a monotypic genus and this distinction warranted its further investigation. Two new coumarins, (+)-trachypleuranin-A and (±)-trachypleuranin-B were isolated and identified by spectroscopic and synthetic means.
Keywords: organic chemistry; biochemistry